Participation of visually impaired persons in culture - Beata Szabała (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Cultural activity of visually impaired persons plays an essential role in their rehabilitation. It allows them, among other things, to understand themselves and learn about their own predispositions, develop creative skills, reduce upsetting emotional tensions related to their disability and  create long-lasting bonds with society. Therefore, it is worth taking a closer look at these forms of  participation in which visually impaired or partially sighted are involved. Their characteristic was conducted on the basis of a dichotomous division into reception and creativity. Taking into account these two areas, there are indications of strategies aimed at bringing culture closer to people with visual impairment.